Penentuan Harga Pokok Penjualan Pada Toko Putri Tani Sejahtera Menggunakan Aplikasi Berbasis Web - Dama Mustika; Ernawati Ernawati (Journal of Applied Accounting and Business, 2020)
Research conducted this time aims to analyze the calculation of cost of goods sold as a bencmark to determine the selling price of products produced by the company in order to know the income of each period obtained Putri Tani Sejahtera. With the conduct of this research, it can be seen that the calculation of cost of goods sold by the company is correct and lower that the selling price can potentially earn profits, but determination of the selling price made less focused because it has not done the classification of costs to determine the amount of costs to be charged on the product produced, also the excessive use of materials affects the income of each period. So with the present research is expected to provide improvements to the company. Other than that in conducting this study the data obtained from the company analyzed and compared in accordance with the existing theory.The method used by the author is data collection analysis and designing the system based on the results of research conducted. The development of information system for determining the cost of goods sold uses the waterfall model and the data flow model used is DFD (Data Flow Diagram). Programing language using PHP, and Mysql database keywords cost goods sold, profit, waterfall.